Design and Performance of Magnetic Abrasive Finishing Set Up for Finishing of Extended Surfaces - Farwaha, Harnam Singh; Khangura , Sehijpal Singh; Singh, Gurpreet (Asian Review of Mechanical Engineering, 2016)
Some of the materials used in modern industries and industrial applications are difficult to finish with high accuracy and minimal surface defects using conventional machining and polishing techniques. Use of traditional machining techniques for finishing of these materials may lead to various defects like micro cracks, errors in work piece geometry and work piece surface distortions. Due to the these limitations of the traditional machining processes, there was need of new family of machining and finishing methods known as non-traditional or modern machining methods has been developed. Among the various non-traditional processes, magnetic abrasive finishing is one. This process is used to machine and finish material surfaces that are otherwise very difficult to finish. The aim of this research article, To design and develop a Magnetic abrasive finishing set up for finishing of extended plane surfaces and to finish thin sheets (3-5mm), as finishing of thin sheets is difficult by conventional method like grinding due to high temperature generated by large grinding forces.